Ketepatan Smash Pemain Bolavoli Siswa SMA Ditinjau dari Koordinasi Mata-Tangan dan Extensi Togok - Ever Sovensi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga, 2018)
The research objective was to determine the accuracy of volleyball players' smashes in terms of eye-hand coordination and EXTENSI TOGOK. This is correlation study. The population was all of the volleyball players in SMAN 2 South Bengkulu consist of 15 females and 30 males. Meanwhile,the sampling was purposive sample which was only all of the male players. The location of the study was volleyball field at SMAN2 South Bengkulu and conducted on november 2011. The data of hand-eye coordination was taken by using ball warfen und-fangen test, EXTENSI TOGOK by bridge up test and smash accuracy by diagonal and frontal smash test. The technique of data analysis used normality testing, simple correlation analysis and multiple correlation. It can be concluded that 1) there was significant relationship between hand-eye coordination and smash accuracy of volleyball players of SMAN 2 South Bengkulu; 2) there was significant relationship between EXTENSI TOGOK and smash accuracy of volleyball players of SMAN 2 South Bengkulu; and 3)there was significant relationship between both hand-eye coordination and EXTENSI TOGOK and smash accuracy of volleyball players of SMAN 2 South Bengkulu. Keyword: Smash, Hand Eyes, Extensi Togok